Socioenvironmental networks and international cooperation: The Global Alliance for Recycling and Sustainable Development- GARSD - Ziglio, Luciana Aparecida Iotti; Ribeiro, Wagner Costa (Sustainability in Debate, 2019)
Networks of nongovernmental organizations dedicated to socio-environmental issues have emerged in recent decades. The involvement of these networks in the international sphere has enabled new approaches to international cooperation. This article introduces the concept of international cooperation and the Global Alliance for Recycling and Sustainable Development (GARSD), a socio-environmental network created by a coalition of NGOs dedicated to promoting recycling of municipal solid waste. This article is the result of a doctoral study conducted using documentary analysis, participant observation and other qualitative data collection methods. The study conclusively finds that it is neessary to analyze the work of these non-state actors within the context of international cooperation between nation states and the possibility of (re)creating political-territorial arrangements, such as networks comprising a variety of actors especially geared towards socio-environmental issues.